Improving the operation of an asymmetric inverter with magnetically coupled inductors for energy storage systems - D. V. Martynov; Y. V. Rudenko; V. V. Martynov (Electrical engineering & Electromechanics, 2025)
Introduction. Bidirectional DC-DC converters are widely used in energy storage systems for efficient energy transfer. One of the effective converters for such systems is the asymmetric inverter with a magnetically coupled inductors. To enhance the efficiency of this converter for energy storage applications, it is necessary to optimize its parameters. Objective. The objective is to develop a mathematical model of an asymmetric inverter with magnetically coupled inductors and based on this model, to establish the conditions for improving the energy efficiency of the inverter in energy storage systems. Methods. The study uses the state-space averaging method and simulation modelling to analyse operational processes. Results. Analytical expressions were derived for calculating current parameters of the magnetically coupled inductor within switching intervals. A correlation was identified between the inductor’s inductance and power source parameters under conditions that eliminate circulating currents, thus reducing static energy losses in the inverter. Novelty. Based on these expressions, new analytical and graphical dependencies were established, illustrating relationships between the inductor parameters and the magnetic coupling coefficient of its windings. These dependencies determine the boundaries of the discontinuous conduction mode for the asymmetric inverter with a magnetically coupled inductors within its switching range. Practical value. The application of these dependencies during the design phase allows for a reduction in both static and dynamic energy losses in the inverter using discontinuous conduction mode. This will also improve the dynamics of transient processes during changes in the direction of energy flow, which is a significant advantage in the development of hybrid power systems for electric vehicles. References 19, figures 9.